Periodic micromagnetic finite element method - Ai, Fangzhou; Duan, Jiawei; Lomakin, Vitaliy (Journal of magnetism and magnetic materials, 2025)
The periodic micromagnetic finite element method (PM-FEM) is introduced to solve periodic unit cell problems using the Landau–Lifshitz–Gilbert equation. PM-FEM is applicable to general problems with 1D, 2D, and 3D periodicities. PM-FEM is based on a nonperiodic FEM-based micromagnetic solver and extends it in several aspects to account for periodicities, including the computation of exchange and magnetostatic fields. For the exchange field, PM-FEM modifies the sparse matrix construction for computing the Laplace operator to include additional elements arising due to the periodicities. For the magnetostatic field, the periodic extensions include modifications in the local operators, such as gradient, divergence, and surface magnetic charges, as well as the long-range superposition operator for computing the periodic scalar potential. The local operators are extended to account for the periodicities similar to handling the Laplace operator. For the long-range superposition operator, PM-FEM utilizes a periodic Green’s function (PGF) and fast spatial convolutions. The PGF is computed rapidly via exponentially rapidly convergent sums. The spatial convolutions are accomplished via a modified fast Fourier transform based adaptive integral method that allows calculating spatial convolutions with nonuniform meshes in O(NlogN) numerical operations. PM-FEM is implemented on CPU and GPU based computer architectures. PM-FEM allows efficiently handling cases of structures contained within the periodic unit cell touching or not touching its boundaries as well as structures that protrude beyond the unit cell boundaries. PM-FEM is demonstrated to have about the same or even higher performance than its parent nonperiodic code. The demonstrated numerical examples show the efficiency of PM-FEM for highly complex structures with 1D, 2D, and 3D periodicities. •Finite element method micromagnetic solver with periodic boundaries is introduced.•Arbitrary 1D, 2D, and 3D periodic boundary conditions are allowed at high accuracy.•The method is based on superposition integrals with no need in air layers.•High performance is achieved on CPUs and GPUs.•Large highly complex problems can be handled.